Association of zinc deficiency and clinical symptoms, inflammatory markers, severity of COVID-19 in hospitalized children - Perestiuk, Vita; Kosovska, Tetyana; Volianska, Liubov; Boyarchuk, Oksana (Frontiers in Nutrition, 2025)
IntroductionZinc plays an important role in the functioning of the immune system. Zinc deficiency leads to increased susceptibility to inflammatory and infectious diseases. There are few studies investigating the role of zinc in the development and progression of COVID-19 in children, and their findings remain inconsistent. This study aimed to determine the zinc levels in children with COVID-19 and assess their association with symptoms, inflammation markers, and disease progression.MethodsA prospective cohort study included hospitalized patients under 18 years who had a confirmed diagnosis of SARS-CoV-2 infection. Serum zinc concentrations were measured using a colorimetric method. Based on zinc levels, the children were divided into two groups: the first group had concentrations below 10.7 μmol/L, indicating zinc deficiency, while the second group had levels above 10.7 μmol/L, which was considered within the optimal range.ResultsIn total, 140 hospitalized patients with COVID-19 were examined. Zinc deficiency was identified in 40 children (28.6%), while optimal levels were found in 100 children (71.4%). Zinc status did not depend on the age of the children. Among the symptoms of acute SARS-CoV-2 infection, children with zinc deficiency showed a trend toward more frequent fever occurrences (p = 0.0654). No significant impact of zinc status was observed on the severity of COVID-19 or the duration of hospitalization. Children with zinc deficiency had higher median values of the neutrophil-to-lymphocyte ratio (NLR) (1.84 vs. 1.09, p = 0.0010), C-reactive protein (CRP) levels (9.65 vs. 3.96 mg/L, p = 0.0053), and fibrinogen levels (2.88 vs. 2.07 g/L, p = 0.0057) compared to those with adequate zinc levels. Additionally, the percentage of patients with a NLR greater than 4, elevated CRP, and fibrinogen levels was higher in the zinc-deficient group (p = 0.0017, p = 0.0107, p = 0.0338, respectively).ConclusionZinc deficiency was observed in 28.6% of children with COVID-19 and was not dependent on age. Children with hypozincemia had higher levels of inflammation markers, including the neutrophil-to-lymphocyte ratio and CRP.